Biopsychosocial approach to understanding predictors of depressive symptoms among men who have sex with men living with HIV in Selangor, Malaysia: a mixed methods study protocol - Mohamad Fisal, Zul Aizat; Abdul Manaf, Rosliza; Fattah Azman, Ahmad Zaid; Karpal Singh, Gurpreet Kaur (Public Library of Science (PLoS), 2023)
Background: Depression is the most common psychiatric disorder reported among patients living with Human Immunodeficiency Virus (HIV), resulting from the intricate combination of biological, psychological, and social factors. Biopsychosocial factors can significantly impact the psychological well-being of men who have sex with men (MSM) living with HIV through social stigma, access and compliance to care, economic insecurity, relationship difficulties, and risky behavior. Compared to MSM without HIV, MSM living with HIV were more likely to be depressed. Despite specific vulnerabilities and health needs, MSM living with HIV remain understudied and under served in Malaysia owing to legal, ethical, and social challenges. Objective This is merely a published protocol, not the findings of a future study. This study aims to determine and explain the predictors of depressive symptoms among MSM living with HIV. Specifically, this study wants to determine the association between depressive symptoms among MSM living with HIV and biological, psychosocial, and social factors. Finally, the mixed methods will answer to what extent the qualitative results confirm the quantitative results of the predictors of depressive symptoms among MSM living with HIV. Methods: The study has ethical approval from the Medical Research Ethics Committee (MREC) of the Ministry of Health (MOH) NMRR ID-21-02210-MIT. This study will apply an explanatory sequential mixed methods study design. It comprised two distinct phases: quantitative and qualitative study design for answering the research questions and hypothesis. This study will randomly recruit 941 MSM living with HIV in the quantitative phase, and at least 20 MSM living with HIV purposively will be selected in the qualitative phase. The study will be conducted in ten public Primary Care Clinics in Selangor, Malaysia. A self-administered questionnaire will gather the MSMs background and social, psychological, and biological factors that could be associated with depressive symptoms. For the quantitative study, descriptive analysis and simple logistic regression will be used for data analysis. Then, variables with a P value < 0.25 will be included in multiple logistic regression to measure the predictors of depressive symptoms. In the qualitative data collection, in-depth interviews will be conducted among those with moderate to severe depressive symptoms from the quantitative phase. The thematic analysis will be used for data analysis in the qualitative phase. Integration occurs at study design, method level, and later during interpretation and report writing. Result: The quantitative phase was conducted between March 2022 to February 2023, while qualitative data collection is from March 2023 to April 2023, with baseline results anticipated in June 2023. Conclusion: In combination, qualitative and quantitative research provides a better understanding of depressive symptoms among MSM living with HIV. The result could guide us to provide a comprehensive mental healthcare program toward Ending the AIDS epidemic by 2030.